Plasma parameters of microarcs towards minuscule discharge gap. Issue 9 (10th June 2020) - Baeva, Margarita; Loffhagen, Detlef; Becker, Markus M.; Siewert, Erwan; Uhrlandt, Dirk
Abstract: This paper describes the behaviour of the plasma parameters of microarcs generated between a cooled copper anode and a ceriated tungsten cathode by means of a one‐dimensional unified non‐equilibrium model for gap lengths between 15 and 200 μm and current densities from 2 × 10 5 up to 10 6  A/m 2 . The results obtained show that the decrease of the gap length to a few tens of micrometres for a given current density results in a progressive shrinking of the quasi‐neutral bulk in the microplasma and its complete disappearance. The decrease of the gap length further leads to an increase of the discharge voltage and the electron temperature and to slightly less heating of the gas. Abstract : The small extent of the regions of space charge adjacent to the electrodes in direct current electric arcs causes considerable difficulties in the exploration of the plasma properties therein. The spatially one‐dimensional unified non‐equilibrium modelling of microarc discharges applied in this work provides the opportunity to have a deeper insight into the behaviour of the plasma properties at decreasing gap lengths towards a pure space‐charge form of the microarc.